Hubungan Kualitas Pelayanan, Citra Merek, Kepuasan Pelanggan, Terhadap Loyalitas Pelanggan - Nely Maulina M; Anak Agung Ketut Diatmika (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
A business had a primary goal of gaining a competitive advantage by creating good customer value. The characteristics that influenced customer loyalty were explored in this study because they provided benefits to the company. This study aimed to explore the relationship between service quality, brand image, customer satisfaction, and customer loyalty in the context of online purchases through the Gofood application. Using a descriptive causality design and quantitative methods, as well as purposive sampling techniques, data were collected from 145 Gofood user respondents and analyzed using Partial Least Square-Structural Equation Modeling (PLS-SEM). The analysis results show that service quality and brand image have a significant impact on customer satisfaction, which in turn significantly affects customer loyalty. Customer satisfaction also has a significant positive impact on customer loyalty in the GoFood application.